The Students' Motivation in Learning English Offline after Pandemic: A Study at State Senior High Schools in Bintuhan City Kaur Regency - Beti Yusipa; Ira Maisarah; Azwandi Azwandi (Edu-Ling: Journal of English Education and Linguistics, 2022)
Abstract The goal of this study was to understand the causes of students' low motivation to learn English. This study employed a descriptive quantitative approach. Documentation, interviews, observations, and questionnaires are the research's primary. Students in State Senior High Schools in Bintuhan City Kaur Regency are the focus of this study. As a result of the research, students are highly motivated to learn English offline following the epidemic in reading types with intrinsic points. Students so like reading things that interest and make them pleased. Key word : motivation, intrinsic, extrinsic, students